Design and Development of A Web-Based Point Of Sale (POS) Information System for Ngadi Rejo Store - Wijaya, Yohan; Tanamal, Rinabi (Soegijapranata Catholic University, 2025)
The The advancement of information technology has had a significant impact on the business world, providing added value as well as new challenges. This study involves Toko Ngadi Rejo, which has seen an increase in the variety of Jamu products. However, manual stock recording has caused data discrepancies and reduced employee productivity. Therefore, the author proposes the design of a web-based stock and sales management application using the Laravel framework with database integration.The research method includes needs analysis through observation and interviews, system design using flowcharts and ERD (Entity Relationship Diagram), and the implementation of a web-based application. The developed system includes stock management, sales recording, and real-time reportingThe research results show that this system improves the efficiency and accuracy of stock recording. User testing using the user experience questionnaire (UMUX) indicates positive responses from users. The implementation of this system is expected to reduce recording errors, increase productivity, and facilitate stock and sales management.Thus, this web-based stock and sales management application is expected to be an effective solution for Toko Ngadi Rejo, supporting the future growth of their business.